Biomimetic mineralization: encapsulation in calcium carbonate shells - Oliveira, Susana Costa de (2015)
Calcium carbonate biomineralization is a self-assembly process that has been studied to be applied in the biomedical field to encapsulate biomolecules. Advantages of engineering mineral capsules include improved drug loading efficiencies and protection against external environment. However, common production methods result in heterogeneous capsules and subject biomolecules to heat and vibration which cause irreversible damage. To overcome these issues, a microfluidic device was designed, manufactured and tested in terms of selectivity for water and oil to produce a W/O/W emulsion. During the development of this work there was one critical challenge: the selective functionalization in closed microfluidic channels. Wet chemical oxidation of PDMS with 1M NaOH, confirmed by FTIR, followed by adsorption of polyelectrolytes - PDADMAC/PSS - confirmed by UV-Vis and AFM results, render the surface of PDMS hydrophilic. UV-Vis spectroscopy also confirmed that this modification did not affect PDMS optical properties, making possible to monitor fluids and droplets. More important, with this approach PDMS remains hydrophilic over time. However, due to equipment constrains selectivity in microchannels was not achieved. Therefore, emulsion studies took place with conventional methods. Several systems were tried, with promising results achieved with CaCO3 in-situ precipitation, without the use of polymers or magnesium. This mineral stabilizes oil droplets in water, but not in air due to incomplete capsule formation.